Pileup mitigation at CMS in 13 TeV data - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2020, 2020)
Title screen